BIOMONITORING OF ATMOSPHERIC HEAVY METAL POLLUTION USING LICHENS AND MOSSES IN THE CITY OF ISTANBUL, TURKEY - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2009)
This paper presents the analysis of air pollutants in naturally growing a lichens and mosses sampled at 10 urban and suburban sites in the city of Istanbul, Turkey. Ten elements (Al, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Zn) were measured in the thalli of eight lichen species (Cladonia spp., Evernia prunastri, Flavoparmelia caperata, Hypogymnia tubulosa, Parmelia sulcata. Physcia adscendens, Xanthoparmelia tinctina, Xanthoria parietina) and three moss species (Didymodon vinealis, Hypnum cupressifome, Pylaisia polyantha) using Atomic Absorption Spectrometry (AAS). Based on the analysis of the lichen samples, the heavy metal concentrations from the highest to the lowest areas follows: Mn > Zn > Pb > Cu > Al > Ni > Cr > Fe > Co > Cd. The elemental composition of lichens and mosses can be used as biomonitor value to indicate air pollution levels in the city.
Keywords: lichen; moss; biomonitor; metals; Istanbul; pollution; ELEMENT CONCENTRATIONS; AIR-QUALITY; DEPOSITION; REGION; PROVINCE